Effectiveness of Using Illustrated Flash Cards in Overcoming Reading Difficulties in First Grade Elementary School Students - Dalimunte, Nur Aisyah; Kusumawati, Tri Indah (Journal of Social Work and Science Education, 2025)
This study was conducted on first-grade students at State Elementary School 101873 with the aim of identifying the strategies implemented by the school to improve students’ reading skills. The research employed a quantitative approach using a quasi-experimental method designed through a Pre-test-Post-test Control Group Design. In this design, the students were divided into two groups: the experimental group, which received instruction using picture flashcards, and the control group, which received instruction through conventional teaching methods. Sampling was carried out using a random sampling technique. Standardized research instruments, such as reading tests and direct observation, were utilized. To assess changes or improvements in reading ability, both pre-test and post-test were administered. The data from the pre-test and post-test were analysed to evaluate the effectiveness of using picture flashcards in reading instruction. The results of the paired sample correlation test showed a significant relationship between pre-test and post-test scores in both the experimental and control groups, with significance values of 0.26 and 0.00, respectively. A significance value greater than 0.00 indicates a meaningful correlation between the pre-test and post-test results in both groups. Furthermore, a normality test was conducted on the pre-test and post-test data to ensure that the data followed a normal distribution. In the experimental group, the significance values were 0.638 for the pre-test and 0.320 for the post-test, indicating that the data were normally distributed. Similarly, in the control group, the significance values were 0.072 for the pre-test and 0.129 for the post-test, also confirming a normal distribution of the data. Thus, this study provides empirical evidence that the use of picture flashcards has the potential to serve as an effective strategy for improving reading skills among elementary school students.